Ophthalmic Manifestations of Immunoglobulin G4-Related Disease (IgG4-RD) - Ayushi Agarwal; Samreen Khanam; Akash Raut; Ruchi Goel (Delhi Journal of Ophthalmology)
Immunoglobulin-G4 related disease (IgG4-RD) is an inflammatory disorder of unknown etiology that comprises a wide spectrum of presentation, involving nearly all the bodily systems. A number of clinical conditions which were previously identified as distinct entities, such as autoimmune pancreatitis, Reidel thyroiditis, and Mikulicz syndrome, have now come within the purview of this disease. The clinical expression of IgG4-RD varies depending upon the organ involved. The authors in this article aim to highlight the various ophthalmic manifestations of IgG4-RD.